(untitled) (Journal of Hama University, 2022)
The aim of the research is to evaluate the effectiveness of Pendulum appliance anchored with mini implants in upper molars distalization and to study the dentoalveolar effects induced by treatment with this device.Pendulum appliance anchored with two palatal mini implants was applied to a sample of (15) patients with class II malocclusion, their ages ranged between (13-15) years. Upper molars distalization was done using the mentioned appliance until a class I molar relationships was obtained with an overcorrection of (1-2) mm. Lateral cephalometric radiographs were performed for all sample members using a (Carestream, CS 9300, France) device, then the dentoalveolar variables following upper molars distalization using Pendulum appliance anchored with mini implants were studied by a (CS Imaging Software, 7.0.23.2D).The use of Pendulum appliance anchored with mini implants resulted in distalization motion of the first and second upper molars of (4.67) mm and (4.27) mm respectively, upper molars distalization motion was associated with a tipping distally of (9)º degrees for the first molars and (9.65)º degrees for the second molars, also the use of the mentioned appliance resulted in distalization motion with slight tipping distally for the first and second upper premolars, whereas the first premolars moved distally by (2.11) mm and tipped distally by (2.91)º degrees, the second premolars moved distally by (2.61) mm and tipped distally (4.51)º degrees, while mesial motion of (0.31) mm with slight tipping mesially of (0.29)º degrees was observed at the level of the upper incisors following the upper molars distalization using Pendulum appliance anchored with mini implants. The results of the current study demonstrated the effectiveness of Pendulum appliance anchored with mini implants in returning upper first molars distally and correcting the relationship of dentoalveolar class II despite the presence of fully erupted upper second molars, also the study demonstrated the occurrence of distalization motion of the first and second premolars, and thus no loss of anchorage during upper molars distalization using the mentioned appliance.